Agent-based models in cellular systems - Pleyer, Jonas; Fleck, Christian (Frontiers in Physics, 2023)
This mini-review discusses agent-based models as modeling techniques for studying pattern formation of multi-cellular systems in biology. We introduce and compare different agent-based model frameworks with respect to spatial representation, microenvironment, intracellular and extracellular reactions, cellular properties, implementation, and practical use. The guiding criteria for the considered selection of agent-based model frameworks are that they are actively maintained, well documented, and provide a model development workflow.